Portrayal of China in the national Urdu-language press of Pakistan - Akber Ali (The Journal of Humanities & Social Sciences, 2022)
Public discourse on China is widespread in Pakistan. How China is depicted in the national press of Pakistan remains to be examined academically. The current study aims to dwell on the images of China in the editorial genres of the popular Urdu press of Pakistan. The findings of the study suggest that contrary to the global media depictions of China, there is an overarching „favorable‟ image of China in the popular press of Pakistan and that that China is predominantly presented as „trustworthy ally‟ of Pakistan. The study found no significant differences in the images of China in the chosen newspapers. The discussion elaborates the possible explanations for the over-arching pro-China frame in the news media of Pakistan. „China is the only country that supports and provides help to Pakistan in all fields of life‟ (Editorial, Nawa-e-Waqt, 10 June, 2015). „Xi‟s visit to Pakistan is a historic‟. (Editorial, Daily Express, April 22, 2015).